Library administrative service strategy on archives and library department in murung raya district - Panjaitan, Hendri; Broto, Mani Festati; Djoko Rahardjo (Institute of Computer Science (IOCS), 2023)
Mobile library services in Murung Raya Regency have not been carried out optimally. One of the main obstacles is geographical conditions, which causes mobile library services to be inefficient. The purpose of this study is to analyze the mobile library services carried out by the Archives and Libraries Office, especially at the mobile library itself. Qualitative descriptive methods are used with SWOT data analysis techniques, as well as Internal Factory Analysis Summary (IFAS) and External Factory Analysis Summary (EFAS) matrices, to determine the position of library administration services. The results of this study indicate that the wide geographical area requires an adequate number of librarians, so that scheduled training is necessary. The low budget allocation from the government makes mobile library services less than optimal, and the low reading interest of the community is a factor that must be improved. To achieve library services, it is necessary to increase collaboration between volunteers and employees, involve employees in visits to new locations, plan to open mini libraries, and use social media to convey important information to the publicMobile library services in Murung Raya Regency have not been carried out optimally. One of the main obstacles is geographical conditions, which causes mobile library services to be inefficient. The purpose of this study is to analyze the mobile library services carried out by the Archives and Libraries Office, especially at the mobile library itself. Qualitative descriptive methods are used with SWOT data analysis techniques, as well as Internal Factory Analysis Summary (IFAS) and External Factory Analysis Summary (EFAS) matrices, to determine the position of library administration services. The results of this study indicate that the wide geographical area requires an adequate number of librarians, so that scheduled training is necessary. The low budget allocation from the government makes mobile library services less than optimal, and the low reading interest of the community is a factor that must be improved. To achieve library services, it is necessary to increase collaboration between volunteers and employees, involve employees in visits to new locations, plan to open mini libraries, and use social media to convey important information to the public.